ANALYSIS OF MSMEs BUSINESS PERFORMANCE BASED ON INTELLECTUAL CAPITAL AND SOCIAL CAPITAL: Case Study on MSMEs in Gorontalo City - Hafid, Radia; Hafid, Fadila; Dai, Sri Indriyani S; Santoso, Ivan Rahmat; Saleh, Sri Endang (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
This study aims to determine the performance of MSMEs businesses in Gorontalo city in terms of financial performance and non-financial performance and to determine the influence of intellectual capital directly and indirectly on the performance of MSMEs businesses in Gorontalo City. The approach in this study is quantitative with a correlational method. Data collection in this study was carried out using a questionnaire. The population in this study was 14,507 people and with the Slovin formula, a sample size of 100 people was obtained. Data analysis in this study was descriptive statistics and SEM-PLS. The results of the study showed that 1) the performance of MSMEs businesses for financial performance indicators is in the less good category with a score of 67.07% and for non-financial performance indicators it has a score of 75.26% which is in the fairly good category; 2) intellectual capital directly has a positive and significant effect on MSMEs social capital; 3) intellectual capital directly has a positive but not significant effect on MSMEs business performance; 4) social capital directly has a positive and significant influence on the performance of MSMEs businesses; 5) intellectual capital through social capital has a positive and significant influence on the performance of MSMEs businesses.